Future of pineapple leaf paper: a review - Mohd Sufian, Amirul Azan; Othman, Siti Amira; Hasrin, Noradriana Izzaty; Harun, Siti Nur Idayu (Academia Industry Networks, 2020)
This paper reviews about the future of pineapple leaf paper by focusing on the properties and potential of pineapple leaf paper. Besides that, environmental issues and quality of pineapple leaf paper as compared with the existing paper in market are also discussed.